# RD Sharma Class 9 Solutions Chapter 6 Factorisation of Polynomials Ex 6.4

In this chapter, we provide RD Sharma Solutions for Chapter 6 Factorisation of Polynomials Ex 6.4 for English medium students, Which will very helpful for every student in their exams. Students can download the latest RD Sharma Solutions for Chapter 6 Factorisation of Polynomials Ex 6.4 Maths pdf, free RD Sharma Solutions for Chapter 6 Factorisation of Polynomials Ex 6.4 Maths book pdf download. Now you will get step by step solution to each question.

### RD Sharma Solutions for Class 9 Chapter 6 Factorisation of Polynomials Ex 6.4 Download PDF

Question 1.
f(x) = x3 – 6x2 + 11x – 6; g(x) = x – 3
Solution:
We know that if g(x) is a factor of p(x),
then the remainder will be zero. Now,
f(x) = x3 – 6x2 + 11x – 6; g(x) = x -3
Let x – 3 = 0, then x = 3
∴ Remainder = f(3)
= (3)3 – 6(3)2 +11 x 3 – 6
= 27-54 + 33 -6
= 60 – 60 – 0
∵  Remainder is zero,
∴ x – 3 is a factor of f(x)

Question 2.
f(x) = 3X4 + 17x3 + 9x2 – 7x – 10; g(x) = x + 5
Solution:
f(x) = 3x4 + 17X3 + 9x2 – 7x – 10; g(x) = x + 5
Let x + 5 = 0, then x = -5
∴  Remainder = f(-5) = 3(-5)4 + 17(-5)3 + 9(-5)2 – 7(-5) – 10
= 3 x 625 + 17 x (-125) + 9 x (25) – 7 x (-5) – 10
= 1875 -2125 + 225 + 35 – 10
= 2135 – 2135 = 0
∵  Remainder = 0
∴ (x + 5) is a factor of f(x)

Question 3.
f(x) = x5 + 3x4 – x3 – 3x2 + 5x + 15, g(x) = x + 3
Solution:
f(x) = x5 + 3X4 – x3 – 3x2 + 5x + 15, g(x) = x + 3
Let x + 3 = 0, then x = -3
∴ Remainder = f(-3)
= (-3)5 + 3(-3)4 – (-3)3 – 3(-3)2 + 5(-3) + 15
= -243 + 3 x 81 -(-27)-3 x 9 + 5(-3) + 15
= -243 +243 + 27-27- 15 + 15
= 285 – 285 = 0
∵  Remainder = 0
∴  (x + 3) is a factor of f(x)

Question 4.
f(x) = x3 – 6x2 – 19x + 84, g(x) = x – 7
Solution:
f(x) = x3 – 6x2 – 19x + 84, g(x) = x – 7
Let x – 7 = 0, then x = 7
∴  Remainder = f(7)
= (7)3 – 6(7)2 – 19 x 7 + 84
= 343 – 294 – 133 + 84
= 343 + 84 – 294 – 133
= 427 – 427 = 0
∴  Remainder = 0
∴ (x – 7) is a factor of f(x)

Question 5.
f(x) = 3x3  + x2 – 20x + 12, g(x) = 3x – 2
Solution: Question 6.
f(x) = 2x3 – 9x2 + x + 12, g(x) = 3 – 2x
Solution:
f(x) = 2x3 – 9x2 + x + 12, g(x) = 3 – 2x Question 7.
f(x) = x3 – 6x2 + 11x – 6, g(x) = x2 – 3x + 2
Solution:
g(x) = x2 – 3x + 2
= x2 – x – 2x + 2
= x(x – 1) – 2(x – 1)
= (x – 1) (x – 2)
If x – 1 = 0, then x = 1
‍∴ f(1) = (1)3 – 6(1)2 + 11(1) – 6
= 1-6+11-6= 12- 12 = 0
‍∴ Remainder is zero
‍∴ x – 1 is a factor of f(x)
and if x – 2 = 0, then x = 2
∴ f(2) = (2)3 – 6(2)2 + 11(2)-6
= 8 – 24 + 22 – 6 = 30 – 30 = 0
‍∴ Remainder = 0
‍∴ x – 2 is also a factor of f(x)

Question 8.
Show that (x – 2), (x + 3) and (x – 4) are factors of x3 – 3x2 – 10x + 24.
Solution:
f(x) = x3 – 3x2 – 10x + 24
Let x – 2 = 0, then x = 2
Now f(2) = (2)3 – 3(2)2 – 10 x 2 + 24
= 8 – 12 – 20 + 24 = 32 – 32 = 0
‍∴ Remainder = 0
‍∴ (x – 2) is the factor of f(x)
If x + 3 = 0, then x = -3
Now, f(-3) = (-3)3 – 3(-3)2 – 10 (-3) + 24
= -27 -27 + 30 + 24
= -54 + 54 = 0
∴ Remainder = 0
∴ (x + 3) is a factor of f(x)
If x – 4 = 0, then x = 4
Now f(4) = (4)3 – 3(4)2 – 10 x 4 + 24 = 64-48 -40 + 24
= 88 – 88 = 0
∴ Remainder = 0
∴ (x – 4) is a factor of (x)
Hence (x – 2), (x + 3) and (x – 4) are the factors of f(x)

Question 9.
Show that (x + 4), (x – 3) and (x – 7) are factors of x3 – 6x2 – 19x + 84.
Solution:
Let f(x) = x3 – 6x2 – 19x + 84
If x + 4 = 0, then x = -4
Now, f(-4) = (-4)3 – 6(-4)2 – 19(-4) + 84
= -64 – 96 + 76 + 84
= 160 – 160 = 0
∴ Remainder = 0
∴ (x + 4) is a factor of f(x)
If x – 3 = 0, then x = 3
Now, f(3) = (3)3 – 6(3)2 – 19 x 3 + 84
= 27 – 54 – 57 + 84
= 111 -111=0
∴ Remainder = 0
∴ (x – 3) is a factor of f(x)
and if x – 7 = 0, then x = 7
Now, f(7) = (7)3 – 6(7)2 – 19 x 7 + 84
= 343 – 294 – 133 + 84
= 427 – 427 = 0
∴ Remainder = 0
∴ (x – 7) is also a factor of f(x)
Hence (x + 4), (x – 3), (x – 7) are the factors of f(x)

Question 10.
For what value of a (x – 5) is a factor of x3 – 3x2 + ax – 10?
Solution:
f(x) = x3 – 3x2 + ax – 10
Let x – 5 = 0, then x = 5
Now, f(5) = (5)3 – 3(5)2 + a x 5 – 10
= 125 – 75 + 5a – 10
= 125 – 85 + 5a = 40 + 5a
∴ (x – 5) is a factor of fix)
∴ Remainder = 0
⇒  40 + 5a = 0 ⇒  5a = -40
⇒ a = −405= -8
Hence a = -8

Question 11.
Find the value of a such that (x – 4) is a factor of 5x3 – 7x2 – ax – 28.
Solution:
Let f(x) =  5x3 – 7x2 – ax – 28
and Let x – 4 = 0, then x = 4
Now, f(4) = 5(4)3 – 7(4)2 – a x 4 – 28
= 5 x 64 – 7 x 16 – 4a – 28
= 320 – 112 – 4a – 28
= 320 – 140 – 4a
= 180 – 4a
∴ (x – 4) is a factor of f(x)
∴ Remainder = 0
⇒  180 -4a = 0
⇒  4a = 180
⇒  a = 1804 =  45
∴  a = 45

Question 12.
Find the value of a, if x + 2 is a factor of 4x4 + 2x3 – 3x2 + 8x + 5a.
Solution:
Let f(x) = 4x4 + 2x3 – 3x2 + 8x + 5a
and Let x + 2 = 0, then x = -2
Now, f(-2) = 4(-2)4 + 2(-2)3 – 3(-2)2 + 8 x ( 2) + 5a
= 4 x 16 + 2(-8) – 3(4) + 8 (-2) + 5a
= 64- 16- 12- 16 +5a
= 64 – 44 + 5a
= 20 + 5a
∴  (x + 2) is a factor of fix)
∴  Remainder = 0
⇒  20 + 5a = 0 ⇒  5a = -20
⇒  a =−205  = -4
∴ a = -4

Question 13.
Find the value of k if x – 3 is a factor of k2x3 – kx2 + 3kx – k.
Solution:
Let f(x) = k2x3 – kx2 + 3kx – k
and Let x – 3 = 0, then x = 3
Now,f(3) = k2(3)3 – k(3)2 + 3k(3) – k
= 27k2 – 9k + 9k-k
= 27k2-k
∴ x – 3 is a factor of fix)
∴ Remainder = 0
∴ 27k2 – k = 0
⇒ k(27k – 1) = 0 Either k = 0
or 21k – 1 = 0
⇒ 21k = 1
∴  k= 127
∴  k = 0,127

Question 14.
Find the values of a and b, if x2 – 4 is a factor of ax4 + 2x3 – 3x2 + bx – 4.
Solution:
f(x) = ax4 + 2x3 – 3x2 + bx – 4
Factors of x2 – 4 = (x)2 – (2)2
= (x + 2) (x – 2)
If x + 2 = 0, then x = -2
Now, f(-2) = a(-2)4 + 2(-2)3 – 3(-2)2 + b(-2) – 4
16a- 16 – 12-26-4
= 16a -2b-32
∵ x + 2 is a factor of f(x)
∴ Remainder = 0
⇒  16a – 2b – 32 = 0
⇒ 8a – b – 16 = 0
⇒ 8a – b = 16         …(i)
Again x – 2 = 0, then x = 2
Now f(2) = a x (2)4 + 2(2)3 – 3(2)2 + b x 2-4
= 16a + 16- 12 + 26-4
= 16a + 2b
∵  x – 2 is a factor of f(x)
∴ Remainder = 0
⇒  16a + 2b = 0
⇒ 8a + b= 0                             …(ii)
⇒ 16a = 16
⇒ a = 1616 = 1
From (ii) 8 x 1 + b = 0
⇒ 8 + b = 0
⇒  b = – 8
∴ a = 1, b = -8

Question 15.
Find α and β, if x + 1 and x + 2 are factors of x3 + 3x2 – 2αx +β.
Solution:
Let f(x) = x3 + 3x2 – 2αx + β
and Let x + 1 = 0 then x = -1
Now,f(-1) = (1)3 + 3(-1)2 – 2α (-1) +β
= -1 + 3 + 2α + β
= 2 + 2α + β
∵  x + 1 is a factor of f(x)
∴  Remainder = 0
∴ 2 + 2α + β = 0
⇒  2α + β = -2                    …(i)
Again, let x + 2 = 0, then x = -2
Now, f(-2) = (-2)3 + 3(-2)2 – 2α(-2) + β
= -8 + 12 + 4α+ β
= 4 + 4α+ β
∵ x + 2 is a factor of(x)
∴ Remainder = 0
∴ 4+ 4α + β = 0
⇒  4α + β = -4 …(ii)
Subtracting (i) from (ii),
2α = -2
⇒  α = −22 = -1
From (ii), 4(-1) + β = -4
-4 + β= -4
⇒  β =-4+ 4 = 0
∴  α = -1, β = 0

Question 16.
If x – 2 is a factor of each of the following two polynomials, find the values of a in each case:
(i) x3 – 2ax2 + ax – 1
(ii) x5 – 3x4 – ax3 + 3ax2 + 2ax + 4
Solution:
(i) Let f(x) = x3 – 2ax2 + ax – 1 and g(x) = x – 2
and let x – 2 = 0, then x = 2
∴ x – 2 is its factor
∴ Remainder = 0
f(2) = (2)3 – 2a x (2)2 + a x 2 – 1
= 8-8a+ 2a-1 = 7-6a
∴ 7 – 6a = 0
⇒  6a = 7
⇒ a = 76
∴ a =  76
(ii) Let f(x) = x5 – 3x4 – ax3 + 3 ax2 + 2ax + 4 and g(x) = x – 2
Let x – 2 = 0, then x=2
∴ f(2) = (2)5 – 3(2)4 – a(23) + 3a (2)2 + 2a x 2 + 4
= 32 – 48 – 8a + 12a + 4a + 4
= -12 + 8a
∴ Remainder = 0
∴ -12 + 8a = 0
⇒ 8a= 12
⇒ a = 128 = 32
∴ Hence a = 32

Question 17.
In each of the following two polynomials, find the values of a, if x – a is a factor:
(i) x6 – ax5 + x4-ax3 + 3x-a + 2
(ii) x5 – a2x3 + 2x + a + 1
Solution:
(i) Let f(x) = x– ax5+x4-ax3 + 3x-a + 2 and g(x) = x – a
∴ x – a is a factor
∴ x – a = 0
⇒ x = a
Now f(a) = a6-a x a5 + a4-a x a3 + 3a – a + 2
= a6-a6 + a4-a4 + 2a + 2
= 2a + 2
∴ x + a is a factor of p(x)
∴ Remainder = 0 Question 18.
In each of the following, two polynomials, find the value of a, if x + a is a factor.
(i)  x3 + ax2 – 2x + a + 4
(ii) x4 – a2r + 3x – a
Solution:

Question 19.
Find the values of p and q so that x4 + px+ 2x2 – 3x + q is divisible by (x2 – 1).
Solution:  Question 20.
Find the values of a and b so that (x + 1) and (x – 1) are factors of x4 + ax3 3x2 + 2x + b.
Solution: Question 21.
If x3 + ax2 – bx + 10 is divisible by x2 – 3x + 2, find the values of a and b.
Solution:

Question 22.
If both x + 1 and x – 1 are factors of ax3 + x2 – 2x + b, find the values of a and b.
Solution: Question 23.
What must be added to x3 – 3x2 – 12x + 19 so that the result is exactly divisibly by x2 + x – 6?
Solution:

Question 24.
What must be subtracted from x3 – 6x2 – 15x + 80-so that the result is exactly divisible by x2 + x – 12?
Solution:  Question 25.
What must be added to 3x3 + x2 – 22x + 9 so that the result is exactly divisible by 3x+ 7x – 6?
Solution:   All Chapter RD Sharma Solutions For Class 9 Maths

—————————————————————————–

All Subject NCERT Exemplar Problems Solutions For Class 9

All Subject NCERT Solutions For Class 9

*************************************************

I think you got complete solutions for this chapter. If You have any queries regarding this chapter, please comment on the below section our subject teacher will answer you. We tried our best to give complete solutions so you got good marks in your exam.

If these solutions have helped you, you can also share rdsharmasolutions.in to your friends.